2000
DOI: 10.1093/gerona/55.6.m329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging on Cardiovascular Responses to Gravity-Related Fluid Shift in Humans

Abstract: Background. Fluid shift induced by postural change causes autonomic neural responses of the cardiovascular system that buffer blood pressure fluctuation. The aim of the study was to clarify the effects of aging on cardiovascular autonomic functions in response to gravity-related fluid shift that unloads or loads the baroreceptors in human subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
(20 reference statements)
3
14
0
Order By: Relevance
“…Although the increased cardiac baroreflex delay of ϳ1.3 s in cervical SCI subjects may seem small, it represents an increased latency of ϳ70%, which is not inconsiderable. Similar increases in latency have been seen in other pathological conditions of blood pressure regulation (21)(22)(23)(24) and in the elderly (50), in whom baroreflex responses and blood pressure control are impaired (40,41). However, the cross-spectral estimates of cardiac baroreflex function may or may not be reflected in baroreflex control of sympathetic vascular regulation.…”
Section: Discussionsupporting
confidence: 60%
“…Although the increased cardiac baroreflex delay of ϳ1.3 s in cervical SCI subjects may seem small, it represents an increased latency of ϳ70%, which is not inconsiderable. Similar increases in latency have been seen in other pathological conditions of blood pressure regulation (21)(22)(23)(24) and in the elderly (50), in whom baroreflex responses and blood pressure control are impaired (40,41). However, the cross-spectral estimates of cardiac baroreflex function may or may not be reflected in baroreflex control of sympathetic vascular regulation.…”
Section: Discussionsupporting
confidence: 60%
“…2). This finding is difficult to explain; however, Miwa et al [35] demonstrated that the arterial baroreflex gain for HR deceased with the upright position in young subjects. They suggested that young subjects showed an adaptive response of baroreflex function to the hypovolemic stress, and the decreased sensitivity may maintain a higher HR, compensating for the hypotensive effect of reduced SV during head-up tilt.…”
Section: Discussionmentioning
confidence: 97%
“…Only a few studies [34,35] addressed the age-related differences of the effect of hypovolemic stress on baroreflex sensitivity of the HR. Of interest, the graded LBNP gradually reduced the baroreflex sensitivity of the HR in the young but not in the elderly, in spite of the increased intensity of hypovolemic stress ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…This response may be in part related to an impaired baroreflex function that causes inappropriate autonomic response. 23,24 Critically ill patients with a history of diabetes may be at a higher risk for hemodynamic instability. Autonomic dysfunction increases as diabetic complications worsen.…”
mentioning
confidence: 99%